THE WAYS OF FORMING OF THE SUSTAINABLE DEVELOPMENT MANAGEMENT SYSTEM OF THE RESORT AND RECREATION CLUSTER - Tatiana Vasilievna Rassohina; Alexander Sergeyevich Sokolov (Современная наука и инновации)
System management of sustainable development of resort and recreational cluster is formed on the basis of a global approach defined UNWTO. Identified the main program, the need for implementation.